Wujud Pelestarian Lingkungan Melalui Penyuluhan Pembuatan Produk Totebag Ecoprint pada Siswa Sekolah Dasar Negeri Kedung Peluk 1 - Erliansa Fatmawati; Shabrina Tsalsabela Ivanda; Firda Aisha Salsabila; Amanda Aureliya; Dewi Puspa Arum (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Environmental education has become increasingly important in addressing global ecological challenges. This community service project aimed to cultivate environmental consciousness among elementary school students through the creative technique of ecoprinting. By using natural materials like leaves and flowers to create unique patterns on fabric, students were not only introduced to an artistic process but also gained a deeper appreciation for the natural world. A workshop was conducted at SDN Kedungpeluk 1 Candi Sidoarjo to teach students the basics of ecoprinting. Participants collected natural materials from their surroundings and experimented with various techniques to create personalized tote bags. The results were impressive, showcasing the students' creativity and their ability to transform natural elements into beautiful and functional objects. Beyond the artistic aspect, the project successfully fostered a sense of environmental stewardship among the students.